"Looking with intention": using photographic essays as didactical tool to explore Berlin. Issue 4 (2nd October 2019) - Van Melik, Rianne; Ernste, Huib
ABSTRACT: Although photography has long been acknowledged as an important research method and didactical tool in human geography, we feel the need to redraw attention to this particular form of doing explorative research. Today's society becomes increasingly "ocularcentral", yet this trend seems unparalleled with a rise of photography in academic work. Based on 10-year experience of using photographic essays in our graduate course on Urban and Cultural Geography, we show how taking pictures can enhance active and engaged learning, spark feelings of enchantment, and stimulate critical, reflexive and non-discursive thinking by asking students to translate theory to practice and vice versa. Our students have "looked with intention" how certain geographical theories are "congealed" in Berlin's urban landscape, specifically linking theory to empirical practice and vice versa. Despite the act of photography being inevitably partial, personal, biased, voyeuristic, colonial and possibly unethical, we believe that the enthusiasm and geographical gaze it brings into the classroom outweigh these limitations. The paper illustrates with multiple examples how the embodied practice of photography results in students carefully reflecting on the physical and social world around them and acknowledging the multimodality of the city, not just as built environment but also as a social sphere and lived place.